"High modernism" and its limits – Assessing state incapacity in Putin's Russia, 2000–2008. Issue 3 (September 2017) - Hashim, S. Mohsin
Abstract: This paper uses an analytical framework developed from James C. Scott's concept of state-sponsored "high modernism" to understand the scope and limits of Putin's attempt to reconfigure state-society relations under the guise of "managed democracy." It argues that Kremlin, under Putin's first two presidential terms (2000–2008), attempted to treat society as a reified object separate from the state and as an object of management. The paper analyzes the Russian state's weak regulatory capacity that coexists with its relatively strong coercive and extractive capacities. It is argued that, in spite of accessing vast resources from the energy sector, the state under Putin's presidency was unable to successfully carry out civil service reform or implement critical reforms in the pension and housing sectors. The analytical framework used offers insights into the limits of authoritarian state-crafting and modernization in contemporary Russia.